No Easy Way In - Kalev Aasmäe (Suomen Antropologi)
This article aims to study the impact the 2012 criminalisation of residential squatting in England and Wales has had on the lived experiences and communal logics of squatters in London. Through the story of a former homeless person named Keith, this paper explores how an individual squatter with limited experience tries to navigate the complex communal logics of squatter crews and identify larger networks in order not to lose the roof over his head. Squatters’ needs to frequently move between non-residential buildings and replicate existing social dynamics in new spatial settings increase the pressures on the solidarity and communal ties within crews. Although, to some extent, stratification based on the experiences, skills, networking abilities, competencies, and status of individual squatters has always existed, the context of growing uncertainty has further amplified it. This, in turn, further erodes solidarity amongst squatters, prompting Keith to turn to new methods of securing accommodation.